Lifestyle medicine pillars as predictors of psychological flourishing - Burke, Jolanta; Dunne, Pádraic James (Frontiers in Psychology, 2022)
Positive Psychology Interventions (PPI) are widely applied to improving wellbeing and helping individuals flourish. At the same time, Lifestyle Medicine (LM) offers an opportunity to boost PPI and psychological research, by expanding its capacity beyond psychology, to include the body and social environment. However, little is known about the relationship between LM and positive psychology flourishing models. Flourishing is as a stage of optimal human functioning that goes beyond moderate wellbeing. The objective of this cross-sectional study was to, (1) identify which of the six LM pillars (sleep, physical exercise, eating well, alcohol intake, social engagement, stress management) best-predicted flourishing; (2) examine the relationship between the number of LM pillars used by individuals and flourishing; (3) determine the odds of using LM pillars by flourishers. A total of 1,112 participants, mostly female professionals (73%), aged 40-59 (77%), based in Ireland, completed an online survey. Regression analysis showed that all six LM pillars predicted flourishing as measured by the PERMA Profiler (including the Physical Health component) and the Mental Health Continuum (MHC). Moreover, the chi-square and odds ratio analysis showed that those who flourished were three times more likely to use 3-6 LM pillars than those who were moderately well; and nine times more likely than languishers. The results are discussed in the context of their contribution to enhancing the population’s health and wellbeing.